Experimental Analysis of Intermittent Pumping Effects on Seawater Intrusion - Shumei Zhu; Zhifang Zhou; Adrian D. Werner; Yongqiang Chen (Water Resources Research)
Abstract Time fluctuations of groundwater flux are known to affect solute transport and thus the width and penetration of seawater intrusion. Yet, most theoretical and laboratory studies of the mixed‐convective processes accompanying seawater intrusion assume constant extraction rates, even though real‐world pumping is usually intermittent. In this study, dynamic changes to an experimental saltwater wedge caused by intermittent pumping were explored using sand tank experiments and numerical simulation. Three different aquifer systems were assessed: a homogeneous unconfined aquifer, and two stratified systems (aquifer‐aquitard‐aquifer), with the latter having an aquitard of lower permeability. Both fully and partially penetrating wells were used. The effects of the pumping period and no‐pumping period were explored, with nine laboratory experiments performed in total. The overall finding is that the impact of intermittent pumping is non‐trivial. Under the laboratory conditions, where head was prescribed inland (representative of a surface water body) intermittent pumping allowed larger volumes of freshwater to be extracted before well salinization. This reflects that non‐pumping periods allow the aquifer to recover. Additional experiments and numerical modeling, which reproduced reasonably well the experimental observations, showed that well salinization could be avoided altogether with sufficient periods of recovery. Numerical models were also used to compare intermittent and constant pumping for the same total extraction rate, showing that intermittent pumping caused earlier well salinization compared to constant pumping, although the aquifer contained a greater mass of salt under constant pumping.